Comportamiento de Tres híbridos de maíz (Zea mays) a la aplicación del fertilizante Microessentials SZ, en la zona de Babahoyo, provincia de Los Ríos - Nevárez Chang, Freddy Germán (2011)
The present work of investigation was made in lands of the Experimental Farm “San Pablo” of the Faculty of Farming Sciences of the Technical University of Babahoyo, located in km. 7 ½ of the route Babahoyo - Montalvo, Province of Los Ríos. With geographical coordinateses of west longitude 79º 32' 49 a South latitude 01º' and one 8 altitude of msnm. The geographic center of origin and dispersion of the maize culture is located in the Valley San Juan de Tehuacán, in the denominated Central Table from Mexico to 2,500 ms on the level of the sea. In this place have been rest archaeological of maize plants that, are considered, date from the 7,000 a.C. In the middle of the decade of `50, in excavations in the city of Mexico, to 30 km.